Motivational Differences in Seeking Out Evaluative Categorization Information. (July 2017) - Smallman, Rachel; Becker, Brittney
Previous research shows that people draw finer evaluative distinctions when rating liked versus disliked objects (e.g., wanting a 5-point scale to evaluate liked cuisines and a 3-point scale to rate disliked cuisines). Known as the preference-categorization effect, this pattern may exist not only in how individuals form evaluative distinctions but also in how individuals seek out evaluative information. The current research presents three experiments that examine motivational differences in evaluative information seeking (rating scales and attributes). Experiment 1 found that freedom of choice (the ability to avoid undesirable stimuli) and sensitivity to punishment (as measured by the Behavior Inhibition System/Behavioral Approach System [BIS/BAS] scale) influenced preferences for desirable and undesirable evaluative information in a health-related decision. Experiment 2 examined choice optimization, finding that maximizers prefer finer evaluative information for both liked and disliked options in a consumer task. Experiment 3 found that this pattern generalizes to another type of evaluative categorization, attributes.